Jagged cliffs and stumbling blocks: interest rate pass-through fragmentation during the Euro area crisis - Sarah Holton; Costanza Rodriguez d'Acri (European Central Bank (ECB), 2015)
The financial crisis has been characterised by fragmentation in the transmission of monetary policy, reflected in high dispersion in the cost of bank finance for euro area firms. Using micro-level bank data across a number of euro area countries, we identify individual bank balance sheet characteristics that contributed to this fragmentation. Interest rate pass-through heterogeneity is estimated using an error correction framework, which captures banks' funding constraints and balance sheet structures. Results show incomplete pass-through of changes in money market rates targeted by the central bank to firms' lending rates, with increases in sovereign bond yields affecting the cost of finance for firms, particularly in stressed countries. Individual bank characteristics have an effect on pass-through during the crisis, even after controlling for changes in macroeconomic conditions. The effect is greatest when looking at characteristics that capture bank funding difficulties, suggesting that a recovery in banks' funding capacities is an important element in reducing fragmentation in the transmission of monetary policy.
Keywords: E52; E58; G01; G20; E43; 330; financial crises; Interest rate pass-through; monetary policy transmission